Asymmetric stem-loop–mediated isothermal amplification of nucleic acids for DNA diagnostic assays by simple modification of canonical PCR primers - Mao, Rui; Wu, Xinyao; Miao, Qing; Cai, Ting (Frontiers in Bioengineering and Biotechnology, 2022)
Nucleic acid–based assays have been adopted as mainstream tools for clinical diagnostics, food safety, and environment monitoring with the merits of accuracy, rapidity, and sensitivity. Loop-mediated isothermal amplification (LAMP) is a well-established method to rapidly identify nucleic acids and has gained recognition and been developed for clinical applications in resource-limited areas. However, the needs for specifically designed primer sets and non-specific amplification hinder the development of LAMP-based nucleic acid tests. Here, a promoted method, termed asymmetric stem-loop–mediated isothermal amplification (ASLAMP) by simple modification of canonical PCR primers, was developed to attempt to overcome those drawbacks. The two primers in the ASLAMP reaction can be easily obtained by adding a stem-loop sequence part to one PCR primer at 5′-ends to get the folding primer (FP), then adding the same primer to the counter canonical PCR primer at 5′-ends to get the turn-back primer (TP). The ASLAMP method was demonstrated in detecting the H1N1 gene fragment with merits of simple primer design, short target sequence, and high amplification efficiency. In addition, the ASLAMP method showed similar efficacy compared with LAMP targeting at the same H1N1 gene sequence. Furthermore, Shigella detection monitored by real-time fluorescence and endpoint colorimetric approaches were taken as examples for evaluation of the practical application of the ASLAMP method, both offered 100% sensitivity and specificity. In conclusion, the novel ASLAMP method with simplicity of primer design, low requirement of equipment, efficiency, and rapidity has exhibited its great prospect for establishment of DNA isothermal amplification in point of care application.